2018
DOI: 10.24203/ajeel.v6i4.5446
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quizlet on Vocabulary Acquisition

Abstract: This study concerns with the major objective of foreign language teaching: vocabulary acquisition. The modern trends of teaching and the vast advance of technology enable teachers to use online and mobile applications in a very wide range. The real effect of using such a method need to be measured. Accordingly, this experimental-design study investigated the effect of Quizlet, a rapidly growing application with an online and mobile phone version, on vocabulary acquisition. Two groups of low-level EFL learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 5 publications
9
49
0
5
Order By: Relevance
“…Based on the results of the non-parametric statistical tests, the posttest scores of students in the experimental group were significantly higher than their pre-test scores, which indicated that they improved due to the treatment sessions. This is in line with the results of previous research studies, such as Altiner (2011), Alzeer (2015) and Sanosi (2018), which found that learners who used electronic flashcards for vocabulary learning improved significantly in the post-test when compared to their pre-test scores. This implies that digital flashcards are useful and effective in enhancing vocabulary learning, as claimed by other researchers (Komachali & Khodareza, 2012;Laufer, et al, 2005;McLean, et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the results of the non-parametric statistical tests, the posttest scores of students in the experimental group were significantly higher than their pre-test scores, which indicated that they improved due to the treatment sessions. This is in line with the results of previous research studies, such as Altiner (2011), Alzeer (2015) and Sanosi (2018), which found that learners who used electronic flashcards for vocabulary learning improved significantly in the post-test when compared to their pre-test scores. This implies that digital flashcards are useful and effective in enhancing vocabulary learning, as claimed by other researchers (Komachali & Khodareza, 2012;Laufer, et al, 2005;McLean, et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…They were not part of students' university course, which may cause a decrease in their motivation. Furthermore, another study was conducted with the aim of investigating the effect of Quizlet flashcards on Saudi male EFL students' vocabulary learning (Sanosi, 2018). There was a control group who studied in the regular teaching method.…”
Section: Randwick International Of Education and Linguistics Science mentioning
confidence: 99%
“…By using the Quizlet Application via a smartphone, students may learn the vocabulary independently. This is because the design of Quizlet Application is appropriate for autonomous learners (Sanosi, 2018). Moreover, the Quizlet Application is considered enjoyable by students in learning vocabulary (Lander, 2016).…”
Section: Using Quizlet Application For the Studentsmentioning
confidence: 99%
“…In Japan, there were two publications, namely Dizon (2016) who investigated Quizlet for facilitating Academic Vocabulary List (AVL) learning in a10-week class, and Wright (2016) who explored the flashcard feature of Quizlet; both confirmed positive effects of Quizlet on vocabulary learning. Among low proficiency learners, Sanosi (2018) also found that Quizlet support assisted learners to improve their learning outcomes when measured in pre-and post-test design. One of the most challenging circumstances in vocabulary teaching and learning is limited class-time and Quizlet can help address this issue (Cunningham, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Dizon (2016), who utilized Quizlet for facilitating Academic Vocabulary List (AVL) learning for Japanese EFL learners in a 10-week class, disclosed significant learning outcomes and positive perceptions of Quizlet. The positive effect of Quizlet on vocabulary acquisition was also noted when implemented in a month of vocabulary learning (Sanosi, 2018). Drawn from experiences of teaching intensive English programs at community college and university levels, Cunningham (2017) acknowledges that Quizlet has the potential to serve as learner vocabulary training place outside classhour which can result in the development of learner autonomy; however, teacher's continuous supervision plays a key role in the learning process.…”
Section: Gamification In Vocabulary Learningmentioning
confidence: 99%